Evaluating Patients for Elective Outpatient Foot and Ankle Surgery: Insurance as a Predictor of Patient Outcomes. Issue 6 (December 2019) - Bakhsh, Wajeeh; Childs, Sean; Oh, Irvin; Flemister, Sam; Baumhauer, Judy; Ketz, John
Background. Elective surgical procedures necessitate careful patient selection. Insurance level has been associated with postoperative outcomes in trauma patients. This study evaluates the relationship insurance level has with outcomes from elective foot and ankle surgery. Methods. Retrospective chart review was performed on patients who underwent elective surgery at a single center with 1-year follow-up. Patients were classified by insurance: under-/uninsured (Medicaid, Option plans) versus fully insured. Outcomes included narcotic refills, patient-reported outcomes (PROMIS) of pain, function, and mood, and compliance with follow-up visits. Statistical analysis involved mean comparison and multivariate regression modeling, with significance P < .05. Results. Cohort groups included 220 insured and 47 under-/uninsured. Outcomes between the insured and under-/uninsured groups differed significantly in narcotic refills (0.72 vs 1.74 respectively, P < .01), missed appointments (0.13 vs 0.62, P < .01), and PROMIS results (pain 54.5 vs 60.2; function 44.3 vs 39.5; mood 44.6 vs 51.3; P < .01). The change in PROMIS scores from preoperative to 1-year postoperative were different in pain (−7.3 vs −2.5, P = .03) and function (+6.3 vs +1.3, P = .04). Regression results confirm insurance as a significant factor (coefficient 0.27, P < .01). Conclusion. These results establish that under-/uninsured patients have worse pain, patient-reported outcomes, and functional outcomes after elective foot and ankle surgery, which may inform patient selection. Levels of Evidence: Level III: Retrospective cohort study